2003
DOI: 10.1002/anie.200390099
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Tunneling of Magnetization and Related Phenomena in Molecular Materials

Abstract: Molecules comprising a large number of coupled paramagnetic centers are attracting much interest because they may show properties which are intermediate between those of simple paramagnets and classical bulk magnets and provide unambiguous evidence of quantum size effects in magnets. To date, two cluster families, usually referred to as Mn12 and Fe8, have been used to test theories. However, it is reasonable to predict that other classes of molecules will be discovered which have similar or superior properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
834
0
7

Year Published

2007
2007
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 2,709 publications
(880 citation statements)
references
References 228 publications
21
834
0
7
Order By: Relevance
“…The magnetic properties of the Mn 12 -Ac single crystals were found to be similar to those previously published. 4,6,[14][15][16] We used a relatively large crystal of Mn 12 -Ac that was about 2 mm long and 0.5 mm wide. Smaller crystals did not show magnetic avalanches on sweeping the magnetic field due to rapid escape of heat through the surface ͑i.e., the magnetization relaxes slowly with increasing magnetic field before the avalanche condition is achieved͒.…”
Section: ͑3͒mentioning
confidence: 99%
“…The magnetic properties of the Mn 12 -Ac single crystals were found to be similar to those previously published. 4,6,[14][15][16] We used a relatively large crystal of Mn 12 -Ac that was about 2 mm long and 0.5 mm wide. Smaller crystals did not show magnetic avalanches on sweeping the magnetic field due to rapid escape of heat through the surface ͑i.e., the magnetization relaxes slowly with increasing magnetic field before the avalanche condition is achieved͒.…”
Section: ͑3͒mentioning
confidence: 99%
“…[1][2][3] A uniaxial molecular anisotropy due to the crystal field generated by the surrounding organic ligands may also be present and lead to a spin ground state that is parallel to the anisotropy axis. Molecular magnets are in many ways superior to similar sized magnetic particles as, by their nature, they exhibit ideal monodispersity in size, volume, shape, and charge.…”
Section: Introductionmentioning
confidence: 99%
“…2͑b͔͒ the second and third harmonic components measured at /2 = 2 kHz. ͑The high noise-to-signal ratio prevented us from obtaining reliable 3 data for H z Ͼ 1 kOe.͒ The equilibrium nonlinear susceptibilities, also shown, were obtained by differentiating 1 eq , measured at the lowest frequency /2 = 1 Hz.…”
Section: Results and Modelizationmentioning
confidence: 99%
“…Actually, many experiments have shown that tunneling takes place at those fields where states of opposite orientation are degenerate, H n Ӎ nH 1 ͑n =0,1,2,... with H 1 =2g B D Ӎ 4200 Oe in Mn 12 ͒, whereas it is suppressed for intermediate fields. [6][7][8] Such a resonant tunneling enables the spins to approach faster their equilibrium state, giving rise to steps in the hysteresis loops around H z = H n , 8,9 and to maxima in the linear dynamical susceptibility 1 . In our previous work, 10,11 we found that resonant tunneling at H z = 0 induces an extra contribution to the nonlinear response 3 , making it larger ͑in magnitude͒ than the equilibrium one and having peaks reversed with respect to the classical predictions.…”
Section: Introductionmentioning
confidence: 99%